[(Tô) te falando]: uma análise funcionalista do fenômeno de afirmação no português brasileiro - DIAS, Joice Martins (2025)
This study, developed within the Amazonian Center for Portuguese Semantic Studies (NAESP) at the Federal University of Pará – Abaetetuba Campus, discusses the phenomenon of affirmation, with an emphasis on a non-canonical form of Portuguese, namely: "[(to) te falando]". The study aims to highlight the linguistic evolution that takes place in the language, emphasizing grammatical motivation. Thus, the research is based on the assumptions of Functionalism, as outlined by Bybee (2010), Givón (1995), Neves (2000) and Oliveira (2020). In order to analyze the phenomenon in focus, data collected from screenshots of WhatsApp and Facebook conversations was used in which occurrences such as 'mano vai dá em nada tô te falando' were found, among others. The research aims to enrich grammatical studies of Brazilian Portuguese by providing an analysis of a non-canonical expression related to the phenomenon. of affirmation.